Pembuatan Dan Pengujian Mesin Penumbuk Daging Rendang Suir Kapasitas 1kg/Jam - Yudi Kurniawan; Junaidi Junaidi; Nofriadi Nofriadi (Politeknik Negeri Padang, 2018)
Rendang is a typical food from Minangkabau that must be present in every custom event in Minangkabau, to improve the quality of the rendang meat, processed rendang meat is processed into processed rendang suir meat to improve the quality of its resistance. At this time the process of making rendang meat still uses a manual process which certainly does not fulfill all the desires of consumers, so the meat rending machine is made with a capacity of 1 kg / minute. This machine functions to pound rendang meat so that fiber from meat looks easier to stir. This machine aims to help the process of pulverizing the rendang meat to become flush. In this machine. The drive system is a fixed clutch, which is connected to one another. Making this frame using ST 37 iron whose dimensions are 350 mm x 550 mm x 700 mm. Whereas for the dimensions of pounding rendang suir meat is 10 mm x 200 mm x 350 mm. How it works rendang meat is placed on the bottom pounder. Then press the male clutch pedal so that there is friction between the male and female coupling so that the pulverization process occurs. After the collision results reach the desired release, step on the clutch pedal, then take the mashed meat. The making of rendang suir meat pounder machine begins with identification and field survey of whatever demands for the needs of producers of rendang suir meat. Then the next stage is the determination of several alternative planning, then the determination of the concept of planning, machine calculation, drawing the planning model.